ANALISIS PERSEPSI PERIVIU TENTANG ASPEK MANDATORY DAN NON-MANDATORY YANG MEMPENGARUHI LKPD YANG BERKUALITAS - Indratama, Janitra Yoga; Praptapa, Agung; Sunarmo, Agus (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2018)
This research aims to analyze the reviewer perception of the process of mandatory and non-mandatory aspects that affect the quality of local government financial reports. Mandatory aspect variables according to UU No 15 Tahun 2004 about examination of administration and state financial responsibility, which includes human resources competency, understanding of SAP, adequate disclosures, compliance with laws and regulations and regulations and government internal control system (SPIP) while research data regarding the non-mandatory aspect variables include organizational commitment and organizational culture. The research data was collected by questionnaire which contain structured questions. Populations in this research is 27 OPD in Purbalingga Regency except Sub-district. Sample is selected using census method. Respondents in this study included the Head of OPD and Auditor Inspectorate. The results of this study show that simultaneously the mandatory and non-mandatory aspects significantly influence on quality local government financial reports. Partially mandatory aspects, significantly influence on quality local government financial reports and non-mandatory aspects partially also have a significant effect on quality local government financial reports.